The effectiveness of dialectical behavior therapy compared to integrative psychotherapy in defensive styles and internet addiction - Moeinedini , Maedeh; Lotfi Kashani , Farah; Shafiabadi, Abdollah (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study is aimed to determine the comparison of the effectiveness of dialectical behavior therapy with integrated psychotherapy in defensive styles and Internet addiction. Method: The research method was quasi-experimental with a pretest-posttest design and one-month follow-up with the control group. And the statistical population consisted of all high school students in district one of Tehran province 2017-2018. In this population, 60 students with high scores in Internet addiction were purposefully selected and were placed randomly in two study groups and one control group (20 people in each group). The research tools included the Internet Addiction Test (Young, 1999) and the defense styles of Andrews, Singh, and Bond (2014). The first study group received eight sessions of 90 minutes and one session per week of integrated psychotherapy package of Lotfi, Kashani, and Vaziri (2015), and the second study group received dialectical behavioral therapy package of Linehan (1987). The data were analyzed using repeated measures analysis. Results: The results showed that dialectical behavior therapy intervention is effective on Internet addiction score (F = 61.21, P = 0.001), developed component (F = 4.28, P = 0.046), underdeveloped component (34 F = 6.6, P = 0.017) and neurotic component (F = 4.51, P = 0.041). And integrated psychotherapy intervention is effective on Internet addiction score (F = 54.07, P = 0.001), developed component (F = 10.09, P = 0.003), underdeveloped component (F = 6.80, P = 0.041) and neurotic component (F = 13.44, P = 0.001).This effect has been stable in the follow-up stage. Conclusion: According to the results, it can be concluded that both dialectical therapy and integrated psychotherapy were effective in defense styles and reducing Internet addiction of the participants of the research compared to the control group. But there is no significant difference between the two therapies.